1998
DOI: 10.1089/apc.1998.12.217
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Primary Care Provider's Knowledge of HIV/AIDS Care

Abstract: To respond to the difficulties that community-based providers face in keeping abreast of the rapid changes in HIV-related care, an intensive pediatric HIV mentoring program (Pediatric HIV Miniresidency [MR]) was developed, linking a regional AIDS Education and Training Center (AETC) with an urban children's hospital HIV outpatient care site. The purpose of this study was to evaluate HIV-related knowledge and perceived skills, abilities, and willingness of community-based primary care pediatric providers and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Along with training and supervision, clinical mentoring by providers skilled in HIV management has been identified as a cornerstone of scaling-up antiretroviral treatment in Africa (Zolfo et al, 2010), including for children, and is part of many national scale-up approaches(Cameron et al, 2012; Rustein et al,1998; Morris et al, 2009; Scherzer et al, 2010; Tolleet al,2008). While evidence of a direct effect of clinical mentoring on clinical outcomes is lacking, there is ample evidence for improved HIV outcomes in cohorts of patients managed by specialized or more experienced providers compared to those with less HIV-specific training and experience (Landon et al, 2003; Stone, Mansourati, Poses & Mayer, 2001; Wood et al, 2003), including for nurse-managed cohorts (Callaghan, Ford & Schneider, 2010; Sanne et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Along with training and supervision, clinical mentoring by providers skilled in HIV management has been identified as a cornerstone of scaling-up antiretroviral treatment in Africa (Zolfo et al, 2010), including for children, and is part of many national scale-up approaches(Cameron et al, 2012; Rustein et al,1998; Morris et al, 2009; Scherzer et al, 2010; Tolleet al,2008). While evidence of a direct effect of clinical mentoring on clinical outcomes is lacking, there is ample evidence for improved HIV outcomes in cohorts of patients managed by specialized or more experienced providers compared to those with less HIV-specific training and experience (Landon et al, 2003; Stone, Mansourati, Poses & Mayer, 2001; Wood et al, 2003), including for nurse-managed cohorts (Callaghan, Ford & Schneider, 2010; Sanne et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that an HIV/AIDS stigma reduction intervention for service providers could increase knowledge and awareness of the disease and change attitudes by reducing fear of HIV transmission through everyday contact and increasing level of comfort, confidence, motivation, and willingness to provide care to PLWHA (Buskin et al, 2002;Lalonde et al, 2002;Rutstein et al, 1998;Sowell, Seals, Wilson, & Robinson, 1998). These studies also highlighted the high importance of training service providers in working with HIV/ AIDS and of incorporating HIV/AIDS intervention activities into their routine activities (Buskin et al, 2002;Wu et al, 2002).…”
mentioning
confidence: 99%
“…Attitudinal, behavioral, psychological, and neuropsychiatric factors are of the utmost importance in every phase of the illness process, from the pre-infection risk of contracting the virus through the various clinical disease stages and their effects on the brain (Castellon, Hinkin, & Myers, 2001;Hinkin, Castellon, Atkinson, & Goodkin, 2001), likelihood of co-occurring hepatitis B and hepatitis C (Essock et al, 2003), ice delivery (Knox, Friedrich, Gaies, & Achenbach, 1994;Satriano, Rothschild, Steiner, & Oldham, 1999). Specific educational interventions have been shown to increase providers' knowledge of clinical symptoms and treatment protocols (Lewis, Gallagher, & Gelbier, 1996;Rutstein et al, 1998), increase comfort in working with HIV+ individuals (Panter et al, 2000;Riley & Greene, 1993), decrease provider anxiety (Atkinson, Grant, Lewis, & Sherval, 1996;Highriter, Tessaro, Randall-David, & Quade, 1995;Sowell, Seals, Wilson, & Robinson, 1998), increase skills and abilities (Campbell, Weeks, Walsh, & Sanson-Fisher, 1996;Farquhar, Stein, & Wagner, 1995), and increase willingness to provide treatment (Crawford et al, 1991;Knox et al, 1994;Martin & Murphy, 1997).…”
Section: Continued On Page 288mentioning
confidence: 99%